Genetic Study of Phenylthiocarbamide (PTC) Taste Sensitivity In Population of The Osing in Kemiren Village-Banyuwangi - Indriani, Fenny; Oktarianti, Rike; Wathon, Syubbanul (Universitas Jember, 2021)
The ability to taste phenylthiocarbamide (PTC), is autosomal trait inherited in a simple Mendelian recessive pattern. The frequency of Taster and non-Taster allele is varies in different populations. The purpose of the research is to investigate the prevalence, gene frequency and genotype frequency of taster (T) and non taster (ts of Osing population in Kemiren-Banyuwangi. PTC serial dilution method was used to assess the PTC Taster and non-Taster phenotypes. The Hardy–Weinberg method was used to determine allele frequencies. The total of samples were 227 people, male were 117 and female were 110 with age range of 15–30 years were randomly selected. The result showed that the Osing population as Taster were 210 (92,52%) and non Taster were 17samples (7,48%) . The allele frecuency of Taster (T) was 0,73 and non Taster (t) was 0,27 respectively. The genotype frequency of dominant Taster (TT) was 0,54, heterozygosity Taster (Tt) was 0,39, and genotype of non Taster (tt) was 0,07.